The Anomalous Deuterium Isotope Effect in the NMR Spectrum of Methane: An Analysis in Localized Molecular Orbitals - Sauer, Stephan P. A. (2008)
Anomaly explained: The secondary isotope effect on the carbon–hydrogen indirect nuclear spin–spin coupling constant in methane, which is larger than the primary isotope effect, is explained in terms of contributions to the coupling constant from localized molecular orbitals.